Programming Skills as a Catalyst for Managerial Competence and Everyday Problem-Solving - Katarzyna RAGIN-SKORECKA; Michał TRZISZKA (Communications of International Proceedings, 2025)
The study explores the role of programming skills in shaping managerial competences and their applicability in everyday problem-solving. The motivation for this research lies in the growing importance of digital and algorithmic thinking in Industry 4.0, where organizations increasingly require managers who can apply systematic approaches to decision-making. While previous studies have emphasized the value of programming in STEM education, a gap exists in understanding how management students perceive the usefulness of programming skills both in their professional roles and in daily life. To address this gap, the research employed a questionnaire survey among 121 students of the Faculty of Management Engineering at Poznań University of Technology, asking them to evaluate the extent to which programming skills influence managerial abilities and assist with everyday tasks. The findings indicate that programming is not widely perceived as directly enhancing management competences, with only 30% of respondents recognizing such an impact, and just 8% rating it as essential. Nevertheless, students acknowledged the significant cognitive benefits of programming, particularly in logical thinking, structured problem-solving, and dividing complex tasks into manageable components, all of which were rated highly useful in everyday contexts. These results suggest that programming education offers valuable transferable skills that extend beyond technical contexts. The study highlights the opportunity to enrich management curricula with programming-related elements, thereby fostering algorithmic thinking that supports both professional decision-making and everyday problem-solving.
Keywords: programming skills; management skills; everyday problem-solving; industry 4.0